2018
DOI: 10.3390/en11102779
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Job Role Localization in the Oil and Gas Industry

Abstract: Job role localization is a strategic local content solution used by countries bearing natural resource stocks to maximize the long-term benefits of exploring and producing them. Currently, there is significant variation in how countries and organizations plan and implement local content and job role localization strategies; hence, this paper aims to gather, classify, and discuss relevant literature with a view to identify best practices for future application. After a multi-dimensional discussion of key terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…Potter (1989) defined localization as the practice of replacing expatriates with locals who have the capabilities to perform as efficient as expatriate staff (Law et al, 2009). According to Pegram et al (2018), localization within the HR literature refers to the replacement of expatriate management staff by competent local people. Governments in some countries have employed several strategies and policies to replace expatriates with nationals (Mellahi & Al-Hinai, 2000) including education and training of the native workforce coupled with government tools of quotas, incentives, and partnership programs for private sector organisations (Williams, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Potter (1989) defined localization as the practice of replacing expatriates with locals who have the capabilities to perform as efficient as expatriate staff (Law et al, 2009). According to Pegram et al (2018), localization within the HR literature refers to the replacement of expatriate management staff by competent local people. Governments in some countries have employed several strategies and policies to replace expatriates with nationals (Mellahi & Al-Hinai, 2000) including education and training of the native workforce coupled with government tools of quotas, incentives, and partnership programs for private sector organisations (Williams, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The independent variables were the responses to the 20 questions. The questions were based on the extensive literature review reported [2]. Part 3 included three open-ended qualitative questions which sought opinions, examples and experiences associated to JRL successes, barriers and recommendations.…”
Section: Questionnairementioning
confidence: 99%
“…It is a strategic local content solution used by countries bearing natural resource stocks to maximize the long-term benefits of exploring and producing them. A recent article [2] presented an extensive review of existing literature on local content and localization in the oil and gas (O&G) sector, highlighting how O&G companies have traditionally struggled with the effective measurement, monitoring, and planning of local content and localization. Understanding, evaluating, and explaining the results from metrics is challenging because local content issues are often intangible.…”
Section: Introductionmentioning
confidence: 99%
“…Some local people are employed in the natural gas activities; however, they are few of them who are working at a high level due to low skills and experience (Pegram et al, 2018) The government and other stakeholders put their efforts in providing expertise to the local experts on the natural gas sector expertise (The Minister of Energy, 2018)…”
Section: Creation Of Employment Opportunitiesmentioning
confidence: 99%